Mass fingerprinting and electrophysiological analysis of the venom from the scorpion Centruroides hirsutipalpus (Scorpiones: Buthidae) - Laura L. Valdez-Velázquez; Timoteo Olamendi-Portugal; Rita Restano-Cassulini; Fernando Z. Zamudio; Lourival D. Possani (Journal of Venomous Animals and Toxins including Tropical Diseases, 2018)
Abstract Background Centruroides hirsutipalpus, of the family Buthidae, is a scorpion endemic to the Western Pacific region of Mexico. Although medically important, its venom has not yet been studied. Therefore, this communication aims to identify their venom components and possible functions. Methods Fingerprinting mass analysis of the soluble venom from this scorpion was achieved by high-performance liquid chromatography and electrospray mass spectrometry. Furthermore, the soluble venom and its toxic effects were evaluated extensively via electrophysiological assays in HEK cells expressing human voltage-gated Na+ channels (hNav 1.1 to Nav1.6), CHO cells expressing hNav 1.7, potassium channel hERG 1 (Ether-à-go-go-related-gene) and the human K+-channel hKv1.1. Results The separation of soluble venom produced 60 fractions from which 83 distinct components were identified. The molecular mass distribution of these components varies from 340 to 21,120 Da. Most of the peptides have a molecular weight between 7001 and 8000 Da (46% components), a range that usually corresponds to peptides known to affect Na+ channels. Peptides with molecular masses from 3000 to 5000 Da (28% of the components) were identified within the range corresponding to K+-channel blocking toxins. Two peptides were obtained in pure format and completely sequenced: one with 29 amino acids, showing sequence similarity to an “orphan peptide” of C. limpidus, and the other with 65 amino acid residues shown to be an arthropod toxin (lethal to crustaceans and toxic to crickets). The electrophysiological results of the whole soluble venom show a beta type modification of the currents of channels Nav1.1, Nav1.2 and Nav1.6. The main effect observed in channels hERG and hKv 1.1 was a reduction of the currents. Conclusion The venom contains more than 83 distinct components, among which are peptides that affect the function of human Na+-channels and K+-channels. Two new complete amino acid sequences were determined: one an arthropod toxin, the other a peptide ...